Consistent prokaryotic community patterns along the radial root axis of two Zea mays L. landraces across two distinct field locations - Tyborski, Nicolas; Koehler, Tina; Steiner, Franziska A.; Tung, Shu-Yin; Wild, Andreas J.; Carminati, Andrea; Mueller, Carsten W.; Vidal, Alix; Wolfrum, Sebastian; Pausch, Johanna; Lueders, Tillmann (Frontiers in Microbiology, 2024)
The close interconnection of plants with rhizosphere- and root-associated microorganisms is well recognized, and high expectations are raised for considering their symbioses in the breeding of future crop varieties. However, it is unclear how consistently plant-mediated selection, a potential target in crop breeding, influences microbiome members compared to selection imposed by the agricultural environment. Landraces may have traits shaping their microbiome, which were lost during the breeding of modern varieties, but knowledge about this is scarce. We investigated prokaryotic community composition along the radial root axis of two European maize (Zea mays L.) landraces. A sampling gradient included bulk soil, a distal and proximal rhizosphere fraction, and the root compartment. Our study was replicated at two field locations with differing edaphic and climatic conditions. Further, we tested for differences between two plant developmental stages and two precipitation treatments. Community data were generated by metabarcoding of the V4 SSU rRNA region. While communities were generally distinct between field sites, the effects of landrace variety, developmental stage, and precipitation treatment were comparatively weak and not statistically significant. Under all conditions, patterns in community composition corresponded strongly to the distance to the root. Changes in alpha- and beta-diversity, as well as abundance shifts of many taxa along this gradient, were similar for both landraces and field locations. Most affected taxa belonged to a core microbiome present in all investigated samples. Remarkably, we observed consistent enrichment of Actinobacteriota (particularly Streptomyces, Lechevalieria) and Pseudomonadota (particularly Sphingobium) towards the root. Further, we report a depletion of ammonia-oxidizers along this axis at both field sites. We identified clear enrichment and depletion patterns in microbiome composition along the radial root axis of Z. mays. Many of these were consistent across two distinct field locations, plant developmental stages, precipitation treatments, and for both landraces. This suggests a considerable influence of plant-mediated effects on the microbiome. We propose that the affected taxa have key roles in the rhizosphere and root microbiome of Z. mays. Understanding the functions of these taxa appears highly relevant for the development of methods aiming to promote microbiome services for crops.